SIFAT DAYA SERAP AIR DAN STABILITAS PENYERAPAN AIR HIDROGEL POLIMER KOMPOSIT - Muhamad Nasir (Research Center for Chemistry - LIPI, 2010)
Hydrogel polymer composite has been synthesized by using 10L scale reactor with batch systems. Hydrogel was synthesized by radical polymerization of a mixture of carboxy methyl cellulose, acrylic acid and methylene bis acrylamide as crosslinker. Hydrogel polymer composite was prepared by adding bentonite to polymer hydrogel. Swelling ratio which indicates of water absorption of hydrogel polymer composite was 60 g / g with a standard deviation of 6.2 %. Durability and stability tests for water absorption of hydrogel polymer composite for 15 days showed the swelling ratio is almost constant and hydrogel is quite stable and not broken down quickly. Effect of temperature and salt solution on water absorption as follow; the water absorption at higher temperatures lower than room temperature and the water absorption from the salt solution is lower than the water absorption of pure water. These results show the hydrogel polymer composite is sensitive to temperature and salt solution.Keyword: hydrogel polymer composite, water absorption,hydrogel stability.